Feasibility of sentinel lymph node detection by near-infrared endoscopy in squamous cell carcinoma of the oral cavity: A pilot study - Sievert, Matti; Goncalves, Miguel; Eckstein, Markus; Iro, Heinrich; Koch, M. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: Near-Infrared (NIR) fluorescence imaging is a novel technique for intraoperative sentinel lymph node (SLN) identification. It has demonstrated promising results in several surgical specialties. The study aims to evaluate the feasibility of identifying the SLN by indocyanine green (ICG) enhanced NIR endoscopy in squamous cell carcinoma of the oral cavity (OCSCC). PATIENTS AND METHODS: Seven patients with (cT1-3 N0) OCSCC were included. We injected 1-1.25 ml of ICG (5 mg/ml) at four to five points around the primary. After the elevation of a platysma flap and posterior retraction of the sternocleidomastoid muscle, fluorescence images were taken via IMAGE1 STM NIR/ICG system to define the SLN(s). We sampled fluorescence marked SLN(s) stratified to lymph node levels, followed by level-specified elective neck dissection. RESULTS: The detection of at least one unilateral or bilateral SLN (range 1-5) was possible in every case. The fluorescence signal occurred, on average, 5.0 ± 2.2 minutes after injection. A total of 22 SLN could be identified. Among 331 histo-logically examined lymph nodes we could detect one micrometastasis, which was correctly defined as SLN (1/22). There were no false-negative findings. No adverse reactions to ICG occurred. CONCLUSIONS: Our first results are indicating the concept of SLN concerning OCSCC after the application of real-time NIR fluorescence endoscopy. However, this has to be verified by more extended studies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Indocyanine green; Near-infrared-imaging; Neck dissection; Oral cavity squamous cell carcinoma; Sentinel node biopsy